Transformational leadership style, organizational commitment and workplace spirituality in teacher education division / Fariza Sulam - Sulam, Fariza (2013)
The purpose of this study is to examine relationship between transformational leadership style and organizational commitment. Furthermore, this research was to examine relationship between workplace spirituality and organizational commitment in Teacher Education Division, Ministry Of Education. The respondents were 150 employees in Teacher Education Division in Putrajaya. The survey used questionnaire was adapted and adopted from Multifactor Leadership Questionnaire (MLQ) developed by Bernard M.Bass and Bruce J.Avolio to measure transformational leadership style, however Organization Commitment Survey (OCS) was adopted from Allen and Meyers (1990) and The Meaning And purpose At Work Questionnaires was adopted from Ashmos and Duchon (2000). All the items using Likert scale. All data has been analysed using SPSS version 17.0 with Descriptive and Pearson Correlation. The findings revealed that Idealized Influence and Inspirational Motivation has highest overall mean in transformational leadership style dimension, organizational commitment has been identified at moderate level of overall mean and inner life has highest mean level in workplace spirituality dimensions. Besides, there is no relationship between transformational leadership style and organizational commitment. However, it revealed that there is a positive correlation between workplace spirituality and organizational commitment. Based on the findings, this study also provides recommendations for improvement of management practices and future research.